Rapid semi-quantification of triacylglycerols, phosphatidylcholines, and free fatty acids in the rice bran of one grain - Junko Nagamoto; Ai Sawazaki; Motonori Miyago; Bungo Shirouchi; Mitsukazu Sakata; Li-tao TONG; Toshihiro Kumamaru; Masao Sato (Journal of Integrative Agriculture, 2018)
We developed a microplate assay method for determining the contents of triacylglycerols (TAGs), phosphatidylcholines (PCs), and free fatty acids (FFAs) in the rice bran of one grain using enzymatic reactions. In this method, enzymes from commercially available kits were used. Optimum reaction conditions were established. It was found that Nonidet P-40 was the optimal among the three surfactants used (Triton X-100, Tween 40, and Nonidet P-40) when lipid was dissolved in a reaction solution. Using this method, it was possible to quantify TAGs, PCs, and FFAs in concentration ranges of 7–150, 5–70, and 8–200 mg L−1, respectively. Furthermore, when the TAG contents in the rice bran were measured, the values closely corresponded to those obtained by extracting from large amounts of rice bran. However, sufficient data on the PC and FFA contents in rice bran are not available for valid comparisons. Although this method can accurately quantify the TAG contents in the rice bran of one grain, the accuracy of the PC and FFA contents has not been verified. Hence, future study is necessary.